PENGARUH CIRCULO MASSAGE TERHADAP TEKANAN DARAH PADA PENDERITA HIPERTENSI DI DESA SUKOWONO KABUPATEN JEMBER: The Effect of Circulo Massage on Blood Pressure in Hypertension Patients in Sukowono Village Jember District - Munir, Sirajul; Sasmiyanto; Widada, Wahyudi (ASSYIFA : Jurnal Ilmu Kesehatan, 2024)
Circulo Massage is one of massage or massage with the main target of lymph blood circulation. This study aims to determine the effect of circulo massage on blood pressure in hypertensive patients in Sukowono Village, Jember Regency Research using Pre-experimental design with Pretest – Post test Group design. The population of this study were hypertensive patients in Sukowono Village, Jember Regency with a population of 152 respondents divided into 30. The sampling technique used Simple Random Sampling. The intervention process uses a standardized intervention protocol for circulo massage procedures. The results of the study with the Paired Sample T-Test test (α < 0.05) showed a significant effect between the results of giving circulo massage with pre and post intervention systolic blood pressure measurements in hypertensive patients. The results of the study on the measurement of systolic blood pressure before the intervention obtained an average value of 154.67 mmHg and after the intervention obtained an average value of 146 mmHg. The effect of circulo massage on systolic blood pressure with the Paired Sample T-Test statistical test obtained a p value of 0.0001. The conclusion of this study is that there is a significant effect on blood pressure in hypertensive patients before and after being given circulo massage. Researcher recommendations, it is hoped that future researchers will better control other variables outside the study so as to avoid bias in research.